The Effect of Time Management Skills Training on Psychological Empowerment of Nurses - Ghasemi Hamzehkola, Roqayeh; naderi, Manijeh (Advances in Nursing & Midwifery, 2018)
Abstract: Background: The issue of time management is particular importance in nursing profession, because, the dead time is actually the time which has not been spent with the patient and if it be forgotten during the work, it will have adverse effects on patients. Objectives: The purpose of empowering the staff is to increase the efficiency of individuals and performance improvement in the organization. The current study is conducted by considering the effect of time management skills’ training on psychological empowerment of nurses of a hospital affiliated to Mazandaran University of Medical Sciences in 2016. methods: The study is a quasi-experimental research on which all of the nurses (n=60) of all wards of the selected hospital participated in full number. Spritzer’s (1995) Psychological Empowerment Questionnaire and Hashemizadeh’s Time Management Questionnaire were used to collect data. The questionnaires were completed by subjects before and after holding a training time management skills workshop. The statistical SPSS21 software and descriptive and inferential statistical tests were used to analyze the data. First, the questionnaires were completed by nurses and then time management skills’ training was held as a one-day workshop in two groups, thus all of the nursing staff in different shifts could participate in this workshop. One month after the intervention, time management and psychological empowerment questionnaires were distributed again among the subjects and the data were collected to determine the effectiveness of time management skills’ training on psychological empowerment of nurses. The statistical SPSS21 software and the paired t-test (and also the non-parametric Wilcoxon test) were used to analyze the data. Results: The results of the study showed that total mean scores of time management and psychological empowerment were 76.73and 60.38 respectively, before intervention and 83.85and 66.26 respectively, after intervention which were statistically significant. The results in sum, showed that time management skills’ training influences on psychological empowerment of nurses (p<0.05). Conclusions:The findings of the current study indicated that time management skills’ training caused increasing the psychological empowerment of nursing staff and also caused sense of having a meaningful job, having competence and trust in the staff. Thus, this method is suggested as a strategy to increase the adequacy, competence, belief of an individual to his/her own abilities, sense of being valuable, independence and trust to others and to works of the nurses and also to improve the professional performance of nurse.